Denominazione della persona e appartenenza religiosa. Il nome arabo dei credenti musulmani (Stato, Chiese e pluralismo confessionale, 2016)
Contributo sottoposto a valutazioneSOMMARIO: 1. Premessa - 2. La scelta del nome nella religione e nella tradizione islamica - 3. L’assunzione di un nome in lingua araba da parte dei convertiti - 4. Il divieto di nome islamico e il suo abbandono forzoso come strumento di “integrazione-assimilazione” - 5. L’assunzione del nome nel diritto civile italiano e la possibilità di mutarlo - 6. Diritto internazionale privato e diritto al nome. Name of the person and religious affiliation. The Arabic name of MuslimsThe structure of the name is a set of an element of identity and religious need for the people converted to different religion, who taking in touch with a new religious belief feel the need to reborn in the new faith. Furthermore, for Muslims, possession of Arabic name is prerequisite in order that Allah can recognize them as faithful. Author reconstructs Islamic traditions related to the choice of the name and makes a reference to the obstacles placed between some States for possession of an Arabic name by Muslims to destroy its identity. Finally reports the rules of the Italian civil law on the subject and in those concerned with private international law.